Role theory in symbolic interactionism: Czech Republic, Germany and the EU - Benes̆, Vít; Harnisch, Sebastian (Cooperation and conflict, 2015)
The literature on norm socialization and Europeanization has largely focused on successful norm diffusion, but thus far it has hardly addressed the norm backlas...